Increased CCR7loPD-1hiCXCR5+CD4+ T Cells in Peripheral Blood Mononuclear Cells Are Correlated with Immune Activation in Patients with Chronic HBV Infection - Ya-Xin Huang; Qi-Yi Zhao; Li-Li Wu; Dong-Ying Xie; Zhi-Liang Gao; Hong Deng (Canadian Journal of Gastroenterology and Hepatology)
T follicular helper cells (Tfh cells) affect essential immune pathogenesis in chronic hepatitis B virus (HBV) infection. The CCR7loPD-1hi Tfh subset has a partial Tfh effector phenotype and is associated with active Tfh differentiation, whereas the CCR7hiPD-1lo Tfh subset is a resting phenotype. We recruited 20 healthy volunteers and 77 patients with chronic HBV infection, including those in the immune tolerant (IT) phase (n=19), immune clearance (IC) phase (n=20), low replicative (LR) phase (n=18), and reactivation (RA) phase (n=20). The expression of CD4, CXCR5, PD-1, and CCR7 was detected in T cells from peripheral blood by flow cytometry. The frequency of the CCR7loPD-1hi T subset was significantly higher in the patients than in the healthy controls (14.92±4.87% vs 12.23±2.95%, p=0.018). The frequency of this Tfh subset in the IC group (18.42%±3.08) was increased compared with the IT group (11.94±2.87%, p=0.001) and LR group (13.65±4.93%, p=0.031) and was higher in the RA group than in the IT group (16.03±5.37% vs 11.94±2.87%, p=0.030). We observed a weak positive correlation between the CCR7loPD-1hi Tfh subset population and the alanine transaminase (ALT) level (r=0.370, p=0.001). The CCR7loPD-1h Tfh subset in the chronic HBV-infected patients was elevated to various degrees among the different immune phases. CCR7loPD-1hiCXCR5+CD4+ T cells are correlated with the immune status of chronic HBV infection patients and may be developed as a potential indicator for antiviral treatment.